PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PERPAJAKAN, PELAYANAN FISKUS DAN KETEGASAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris Wajib Pajak Orang Pribadi Yang Melakukan Usaha Yang Terdaftar Di KPP Pratama Semarang Candisari) - Elisa Tri Kristanty, 11.05.52.0090; Setyowati, Widhy (Students Journal of Accounting and Banking, 2015)
The purpose of this study was to analyze the influence of taxpayer awareness, dissemination of taxation, tax authorities and firmness service tax penalties on tax compliance in the city of Semarang. This study used convenience sampling method in sample selection, the criteria for a sample of taxpayers who do business registered in KPP Semarang Candisari. The data used is primary data collected through questionnaires. Questionnaires were distributed and processed as many as 100. This study used multiple regression analysis to test the hypothesis. The results of this study indicate awareness of the taxpayer, socialization tax, service tax authorities and tax penalties firmness positive and significant impact on tax compliance. While the service tax authorities and no significant positive effect on tax compliance.Keywords: Awareness Taxpayer, Socialization Tax, Service Tax Authorities, Firmness Tax Penalties, Tax Compliance